DEVELOPMENT OF THE ACCOUNTING CONSULTING MARKET IN UKRAINE - Matskiv Г.; Raiter Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article examines the functioning of the consulting services market in Ukraine, with a particular focus on the development of accounting consulting. It analyses key indicators of market volume and outlines the main challenges faced by consulting activities in the country. The authors conducted a thorough analysis of the consulting services market using statistical data and explored the impact of the ongoing war on its development. Notably, it has become difficult to accurately assess the size of the Ukrainian consulting services market and its contribution to the economy. This challenge arises from the lack of a classification that recognises consulting as a distinct type of economic activity. The article emphasises the war's effect on both the demand and supply of consulting services. It investigates which market segments were most adversely affected by the conflict, how client requests have evolved, and what new requirements have emerged for consulting services. Additionally, it analyses the supply and demand factors influencing the consulting services market in Ukraine, supported by statistical data and insights into the functioning and legal regulation of the market. It also explores the size and main characteristics of the consulting services market, detailing its structure and key participants. Special attention is given to trends in the industry and the factors affecting its effectiveness. Research indicates that the Ukrainian market for accounting consulting services exhibits characteristics similar to the global market, particularly since a significant share is held by companies that are part of large international firms. A critical issue remains the lack of regulatory clarity regarding this type of activity, which prevents businesses from accurately reporting statistics in this sector. Looking ahead to the post-war period, the prospects for accounting consulting are linked to a growing demand for consulting services as businesses develop new strategies for growth. The establishment of favourable conditions for the consulting industry's development, along with a competitive environment, is directly connected to improvements in the regulatory framework.